Aprotinin vs. tranexamic acid in isolated coronary artery bypass surgery: A multicentre observational study. Issue 5 (May 2017) - Deloge, Elsa; Amour, Julien; Provenchère, Sophie; Rozec, Bertrand; Scherrer, Bruno; Ouattara, Alexandre
Abstract : BACKGROUND: Aprotinin appears to be more efficacious than lysine analogues to reduce bleeding and transfusion of blood products in high-transfusion-risk cardiac surgical patients. However, in isolated coronary artery bypass graft (CABG) surgery, the results from head-to-head trials remain less conclusive. OBJECTIVE: Our objective was to compare the efficacies and safety of aprotinin and tranexamic acid (TXA) in patients undergoing isolated on-pump CABG. DESIGN: A multicentre before-and-after study pooling individual data from published trials and unpublished data from three other databases. SETTING: Four tertiary care teaching hospitals (Haut-Lévêque Hospital in Bordeaux, Pitié-Salpêtrière Hospital and Bichat-Claude Bernard Hospital in Paris, and Laennec Hospital in Nantes). PATIENTS: We included data of 2496 isolated on-pump CABG surgery patients who received either aprotinin between November 2003 and May 2008 ( n  = 1267) or TXA between November 2007 and November 2013 ( n  = 1229). MAIN OUTCOME MEASURES: The primary outcome was total blood loss within 24 h after operation. Secondary outcomes were transfusion of blood products, reoperation for bleeding, renal replacement therapy, ICU length of stay and in-hospital mortality. RESULTS: Adjusted mean (SEM) 24-h blood loss after surgery [483 (11) vs. 634 (11) ml, P  < 0.0001] and the proportion of patients requiring intraoperative blood product transfusion (32.7 vs. 46.5%, P  = 0.01) were lower in aprotinin-treated patients. No difference was observed with regard to reoperations for bleeding, renal replacement therapy and in-hospital mortality. However, patients receiving aprotinin had a significantly shorter adjusted ICU length of stay. CONCLUSION: In patients undergoing isolated CABG, aprotinin was more effective than TXA in reducing postoperative blood loss, and no safety concerns were identified. The benefits of aprotinin should be considered when evaluating the risk of major blood loss and transfusion in patients scheduled for isolated CABG surgery. Abstract : Supplemental Digital Content is available in the text